Multi-emissivity setting in thermal imaging based on visible-light image segmentation - Ding De-hong; Fang Kui; Yu He-xiang; Qian Ke-jun; Chen Yi-neng; Cui Dai-jun (Institute of Advanced Engineering and Science, 2014)
Emissivity is an accuracy influencing factor during infrared temperature measurement which focusing on regular geometry in laboratory under the condition of single emissivity. But in practical application, the target is often irregular with multi-emissivity,, and if following